Analisis dan perancangan user interface dan user experience untuk sistem asuransi karyawan berbasis web menggunakan metode design thinking - Mualfah, Desti; Rajif, Iqbal (Universitas Muhammadiyah Riau, 2023)
In developing a software application design, it is often done without first observing the user. So the result often causes many problems. Inappropriate design of the interface and user experience will cause problems in the application after it is created. User interface and user experience are two things that are very important and cannot be separated. How easy or difficult it is to use a product will of course also have a big influence on the user's experience when they use the product. Using design thinking in creating a product can have a big influence on the UI/UX process. In designing the WorkerLife website, the author used the design thinking method as a solution to solve problems faced by users and carried out usability testing and assessment using SUS (System Usability Scale). When testing website designs. A score of 77.58 was obtained with a good rating so that the design has been successfully created and users do not experience confusion or difficulties when running the website design prototype.